Omics-Based Interaction Analysis Reveals Interplay of Chemical Pollutant (Ozone) and Photoradiation (UVSSR) Stressors in Skin Damage - Hong Zhang; Yiying Dong; Xue Xiao; Xiao Cui; Xuelan Gu (Biology)
The skin acts as the first line of defense against various environmental stressors, such as solar ultraviolet radiation, visible light, pollution particles and ozone. Simultaneous exposure to different stressors is common in everyday life but has been less studied than exposure to single stressors. Herein, the combined effects of a chemical pollutant (ozone) and a UV radiation stressor (UVSSR) were investigated on a 3D pigmented living skin equivalent model. Our results demonstrate that skin lightness (L* value) was significantly decreased by exposure to either UVSSR or ozone alone and that co-exposure to UVSSR and ozone further exacerbated surface darkness, suggesting that these stressors had a significant joint effect. Conventional differential expression analysis showed that, among exposure groups, co-exposure dysregulated the most genes, followed by ozone and UVSSR alone. Omics-based interaction framework (OBIF) analysis showed that most interactive genes following ozone and UVSSR exposure displayed a cooperative effect and had functions related to the skin barrier; these genes with synergistic effects were enriched in biological pathways such as the chronic inflammatory response and the apoptotic signaling pathway. In summary, exposure to ozone in combination with UVSSR showed a joint effect on UVSSR-induced phenotypic changes in the skin; the underlying mechanism was determined by using transcriptome analysis, showing the additive impacts of ozone on UVSSR-induced skin damage, such as cellular stress and inflammatory responses. These findings shed light on how ozone exacerbates UVSSR damage and indicate that the synergistic response genes identified using OBIF analysis may drive the progression of skin damage induced by chemical/photoradiation stress co-exposure.